The Influence of Intrinsic Motivation and Quality of Work Life on Employee’s Performance of Production Units of PT Perkebunan Nusantara XIV Makasar, South Sulawesi. - Muhamad Akbar; Ronny Mangasi Paian (PT. Banjarese Pacific Indonesia, 2024)
This study, held at the Production Unit of PT Perkebunan Nusantara XVI Makasar, South Sulawesi is aimed at analyzing the influence of intrinsic motivation and quality work life on employee’s performance. The sample in this research, which is quantitative in nature, was the employees of the production unit with a total number of 86 respondents. It is done with data analysis method, using multiple linear regressions.The result of this study indicates that the variables of intrinsic motivation and quality of work life simultanneously affect the employee’s performance with a contribution of 37,3%, while the remaining 52,7% is influenced by other factors, which are beyond this study.Partially, intrinsic motivation variables negatively affect and have a significant influence on performance. This is due to the different work cultures in the sector.